2019
DOI: 10.3390/su11174632
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-Assisted Assessment and Attribute-Based Clustering of Forest Wetland Utility in South Korea

Abstract: The aim of this study was to determine the characteristics of forest wetlands by developing factors for site suitability and applying these factors to 107 sites in South Korea. We developed a forest wetland assessment in a Geographic Information Systems (GIS) environment to assess site suitability. We considered 16 factors including slope, elevation, visibility, land ownership, distance to city, and so on. We conducted an expert survey with experts to analyze the relative importance by using the Analytic Hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Many methods can be used to determine the distances between objects. The most frequently used method is the Euclidean method [30,31]. It consists of determining the distance between two objects in space on the basis of the following relationship [32]:…”
Section: Elbow Methodsmentioning
confidence: 99%
“…Many methods can be used to determine the distances between objects. The most frequently used method is the Euclidean method [30,31]. It consists of determining the distance between two objects in space on the basis of the following relationship [32]:…”
Section: Elbow Methodsmentioning
confidence: 99%
“…The algorithm selects the clusters in individual iterations so that the position of the centroids remains constant in the following steps. The stability of the centroid position is determined based on the Euclidean distance [84][85][86][87].…”
Section: Cluster Design Methodsmentioning
confidence: 99%
“…Some of the recent studies conducted in different countries and regions of the world are reviewed in detail in Table 1. It can be observed that AHP has been exploited for various wetland issues such as vulnerability (Ghosh & Das, 2019; Malekmohammadi & Jahanishakib, 2017; Saha & Pal, 2019), restoration (Maleki, Soffianian, Koupaei, Pourmanafi, & Saatchi, 2018; Mao et al., 2019; Qu et al., 2019), ecosystem health (Chen et al., 2019; Das, Pradhan, Shi, & Alamri, 2020; Sun, Tang, Yu, Song, & Wang, 2019; Wu et al., 2018), degradation risk (Jiang, Lv, Wang, Chen, & Liu, 2017), forest suitability (Yun, Kang, Kim, & Kang, 2019) and nutrient filtering (Alamanos & Papaioannou, 2020).…”
Section: Introductionmentioning
confidence: 99%